Addressing idiom avoidance in culturally and linguistically diverse students through biography-driven instruction - Tarabrina, Irina (Kansas State University, 2019)
This experimental study was designed to examine the effect of Biography-driven Instruction strategies on the linguistic phenomenon of idiom avoidance and a discretionary strategy of idiom use employed by Culturally and Linguistically Diverse (CLD) students. The review of the literature on linguistic avoidance behavior revealed that this topic was not widely researched. Less so were the instructional ways to minimize language learners’ discomfort with idioms. Raising awareness of idiom avoidance strategy in language learners was one of the main purposes of this study. This research and its experiment were meant to create a precedent study that would be followed by researchers and teaching professionals to examine, explore, and manage idiom avoidance phenomenon in language learning process. The research question and the hypotheses were examined through the means of quantitative research design. The study was driven by the repeated-measures design. The same study participants have undergone all the conditions of experiment providing the data at multiple points of time. The study participants were English language learners of various cultural and linguistic background. Three targeted vocabulary strategies Foldables, Learn-Draw-Connect, and Vocabulary Quilt were designed to lead to a higher level of student engagement through social and academic collaborations among CLD students. Idioms are a complex linguistic construct for English learners to master. Idiom avoidance might be a learners’ strategy to cover up their discomfort with idioms by not taking risks of making mistakes and thus looking good in the eyes of other people. Biography-Driven Instruction (BDI) strategies were designed to help lower students’ affective filter and alleviate their anxiety caused by learning new language constructs. The use of BDI strategies might lead to greater CLD students’ interest in including idioms into their second language repertoire. That would help them gain idiomatic competence and higher language proficiency. Through quantitative data collection and analysis, it has been discovered that there was no statistically significant effect of the BDI strategies on the frequency of idiom use by study participants. The findings of the study serve as an extension of the theoretical literature. This study might also render an additional support to the theory of idiom avoidance behavior inherent to language learners. The experiment in this study might also enhance understanding of the temporal nature of avoidance that was determined in the previous studies. Avoidance of difficult constructs such as idioms should and can be addressed in the best interests of the CLD students who need to develop language skills that would help them succeed both academically and socially. Finally, this study raises awareness among teachers of avoidance as a cognitive strategy used by CLD students and of the instructional ways to minimize CLD students’ discomfort with idioms. Through this study, language teachers might continue their search of effective ways to teach idioms such as BDI strategies that would help CLD students cope with their idiom phobia. Idiomatic competence is absolutely necessary for CLD students as it makes them more proficient English speakers who successfully integrate the host culture and contribute to the new society.
Keywords: Idiomatic competence; Avoidance; Language teaching; Idioms